2018
DOI: 10.1016/j.gie.2017.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Volume of surgery for benign colorectal polyps in the last 11 years

Abstract: SR for large, complex colorectal polyps is still frequently performed and has remained stable. A small percentage of patients underwent ER attempts before SR, and referral for an additional ER attempt only occurred in a minority of cases. To increase ER attempts, implementation of a regional multidisciplinary referral network should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 35 publications
2
37
1
Order By: Relevance
“…However, the positive predictive value in this study was quite low at 69% (95% CI 57 to 78), which resulted in unnecessary surgery. This was also shown in other studies 19 20. Hence, we can conclude that incorrect optical diagnosis for predicting SM and SMd invasion results in suboptimal use of endoscopic and surgical treatment options, resulting in both overtreatment and undertreatment.…”
Section: Commentssupporting
confidence: 83%
“…However, the positive predictive value in this study was quite low at 69% (95% CI 57 to 78), which resulted in unnecessary surgery. This was also shown in other studies 19 20. Hence, we can conclude that incorrect optical diagnosis for predicting SM and SMd invasion results in suboptimal use of endoscopic and surgical treatment options, resulting in both overtreatment and undertreatment.…”
Section: Commentssupporting
confidence: 83%
“…In Europe, a recent Dutch study showed that patients with large and complex colorectal polyps are still frequently referred for surgical treatment. These referrals should decrease, because colorectal surgery is known to be associated with significantly higher morbidity and mortality rates (34.8% and 1.4%, respectively) than endoscopic treatment [29]. Implementing ESD could reduce the need for surgery for complex polyps in the West.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, despite the higher morbidity-mortality rate of surgical resection, when the first-line endoscopists could not remove benign LPs themselves, they referred patients to a surgeon twice as often as to a more experienced endoscopist (8,14). This led to a non-negligible volume of surgeries for benign LPs, avoidable in 32% to 74% of cases if patients had been referred to expert endoscopists (13,14,21). Surgery was definitely unwarranted in more than 60% of our benign LP patients who were As previously reported, the risk of malignancy was three-fold and two-fold higher for LPs located in the rectum and sigmoid respectively compared with the rest of the colon (31,32).…”
Section: Colonoscopies and Polypsmentioning
confidence: 99%